Is levator trauma an independent risk factor for anal incontinence?. (12th November 2019) - Melendez‐Munoz, J.; Subramanian, N.; Friedman, T.; Dietz, H. P.
Abstract: Aim: To determine the role of levator ani trauma in anal incontinence (AI), whilst controlling for anal sphincter injury. Methods: The records of 1273 patients who had attended a tertiary urogynaecology unit between 1st of January to 31st December 2016 were reviewed. AI was assessed using St Mark's score and visual analogue scale (VAS). Levator muscle and anal sphincter trauma were examined by translabial ultrasound using tomographic imaging, with archived data sets investigated blinded against all clinical data. A complete avulsion was diagnosed if at least three central tomographic slices showed an abnormal muscle insertion, rated separately for each side. A significant anal sphincter defect was diagnosed if at least four out of six slices showed a defect of ≥ 30°. Results: Avulsion was associated with St Mark's score ( P  = 0.005) and VAS bother of AI ( P  = 0.022) both on univariate analysis and when controlling for external anal sphincter (EAS) trauma on translabial imaging, forceps, body mass index (BMI) and age ( P  = 0.011 and P  = 0.04, respectively). AI expressed as a binary variable was significantly associated with avulsion on univariate analysis ( P  = 0.011), although the association became nonsignificant after controlling for anal sphincter trauma, age, BMI and forceps delivery ( P  = 0.084). Conclusion: In this retrospective observational study, we found a weak association between levator ani avulsion and measures of AI, which largely remained significant when controlling for anal sphincter trauma. However, given the large data set, any clinical effect of levator trauma on AI is likely to be minor.